Black butler. XXXI - Toboso, Yana, 1984- (Yen Press, 2022)
"In order to cut off their enemies' lifelines, the Phantomhive staff has scattered in all directions. To the north, Mey-Rin, having infiltrated Baron Heathfiel's manor, engages in battle with the masterful maid, Jane! Meanwhile, in the east, at a sanatorium for veterans, Baldo and Lau receive a rough welcome from the nurse celebrated as a miracle healer"--